Effect of Various Low Temperature Storage Regimens on Placenta Cryoextract Hormone Content - Grischenko, V. I.; Prokopyuk, O. S.; Volkova, N. A.; Perchik, O. A. (Problems of Cryobiology and Cryomedicine, 2004)
Results proved the different low temperature storage regimens to affect the level of certain hormones content in cryopreserved placenta extract (CPE). According to the technological protocol of CPE preparing a one-day storage at â€“20Â°C with further-long term storage under liquid nitrogen temperature was found to be the optimum regimen.